Pengaruh Kualitas Produk Terhadap Minat Berkunjung dan Kepuasan Pengunjung Sebagai Variabel Mediasi di Rumah Makan Ampera 2 Tak Veteran Bintaro Jakarta Selatan - Triono, Freddy; Rahayu, Nurti; Swantari, Anita (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
The restaurant industry is an important sector in the world of tourism and consumption, including in Indonesia. A successful restaurant depends not only on the quality of its food, but also customer satisfaction which encourages repeat visits. This research aims to analyze the influence of product quality on visitor satisfaction and interest in visiting the Ampera 2 Tak Restaurant, as well as testing the role of visitor satisfaction as a mediating variable. The method used is quantitative research with path analysis techniques involving 100 respondents who are visitors who have visited more than once. The research results show that product quality has a significant influence on visitor satisfaction and interest in visiting, both directly and indirectly through satisfaction. Visitor satisfaction acts as a mediator that strengthens the relationship between product quality and visiting interest. Therefore, restaurants need to continue to pay attention to and improve the quality of products and services to create a sustainable positive experience. The advice for restaurant managers is to maintain consistent product quality and provide friendly service, while visitors are advised to provide constructive input to improve their dining experience.